Flavoenzyme catalysed oxidation of amines: roles for flavin and protein-based radicals. (1st August 2005) - Rigby, S.E.; Basran, J.; Combe, J.P.; Mohsen, A.W.; Toogood, H.; van Thiel, A.; Sutcliffe, M.J.; Leys, D.; Munro, A.W.; Scrutton, N.S.
Abstract : Amines are a carbon source for the growth of a number of bacterial species and they also play key roles in neurotransmission, cell growth and differentiation, and neoplastic cell proliferation. Enzymes have evolved to catalyse these reactions and these oxidoreductases can be grouped into the flavoprotein and quinoprotein families. The mechanism of amine oxidation catalysed by the quinoprotein amine oxidases is understood reasonably well and occurs through the formation of enzyme–substrate covalent adducts with TPQ (topaquinone), TTQ (tryptophan tryptophylquinone), CTQ (cysteine tryptophylquinone) and LTQ (lysine tyrosyl quinone) redox centres. Oxidation of amines by flavoenzymes is less well understood. The role of protein-based radicals and flavin semiquinone radicals in the oxidation of amines is discussed.